2017
DOI: 10.2147/ijn.s125281
|View full text |Cite
|
Sign up to set email alerts
|

Combination of graphene oxide–silver nanoparticle nanocomposites and cisplatin enhances apoptosis and autophagy in human cervical cancer cells

Abstract: Background Cisplatin (Cis) is a widely used chemotherapeutic drug for treating a variety of cancers, due to its ability to induce cell death in cancer cells significantly. Recently, graphene and its modified nanocomposites have gained much interest in cancer therapy, due to their unique physicochemical properties. The objective of this study was to investigate the combination effect of Cis and a reduced graphene oxide–silver nanoparticle nanocomposite (rGO-AgNPs) in human cervical cancer (HeLa) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 84 publications
7
75
0
Order By: Relevance
“…Many researchers investigated GO as a platform for nanomaterials such as gold nanoparticles, magnetic nanoparticles, silver nanoparticles, quantum‐dot, and etc . Yuan and Gurunathan synthesized nanocomposites composed of GO‐silver nanoparticles and nanocomposites have synergistic anticancer activity with cisplatin . Those nanocomposites induced apoptosis of cancer cells and accumulated autophagosomes/autophagolysosomes related to ROS generation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Many researchers investigated GO as a platform for nanomaterials such as gold nanoparticles, magnetic nanoparticles, silver nanoparticles, quantum‐dot, and etc . Yuan and Gurunathan synthesized nanocomposites composed of GO‐silver nanoparticles and nanocomposites have synergistic anticancer activity with cisplatin . Those nanocomposites induced apoptosis of cancer cells and accumulated autophagosomes/autophagolysosomes related to ROS generation.…”
Section: Discussionsupporting
confidence: 61%
“…administration because GO drug carriers have low hemolysis activity. Many researchers investigated GO as a platform for nanomaterials such as gold nanoparticles, magnetic nanoparticles, silver nanoparticles, quantum‐dot, and etc . Yuan and Gurunathan synthesized nanocomposites composed of GO‐silver nanoparticles and nanocomposites have synergistic anticancer activity with cisplatin .…”
Section: Discussionmentioning
confidence: 99%
“…33 As shown in Figure 6B, the treatment with HA-Se-PEI@siRNA markedly induced HepG2 cell apoptosis and obtained higher apoptosis rate (~32.7%) compared with Se-PEI@siRNA (~27.7%) and Lipofectamine 2000@siRNA (~17.9%). However, no obvious cell apoptosis was observed in the HA-Se-PEI@ siNC-treatment group, suggesting that the silence of HES5 contributed to the apoptosis of HepG2 cells.…”
Section: Cell Cycle Arrest and Cell Apoptosismentioning
confidence: 81%
“…Silver has been used in our lives throughout history and recently for many medical applications due to its effectiveness in arresting the growth of microorganisms [115]. Recent studies have shown the enormous therapeutic potential of AgNPs against numerous cancer cells by modulating autophagy action as cytotoxic agents or as nanocarriers that, combined with other treatments, deliver therapeutic molecules [116,117]. The toxicity of AgNPs has been suggested as the result of lysosome-dependent silver ion release that leads to massive ROS production.…”
Section: Silver Nanoparticles-induced Toxicity and The Possible Role mentioning
confidence: 99%